Serum Homocysteine Level Is a Predictor of Relapse and Prognosis in Patients With First-Attack Neuromyelitis Optica Spectrum Disorders - Zhang, Jinwei; Li, Yanfei; Zhou, Yongyan; Zhao, Yi; Xie, Haojie; Duan, Ranran; Yao, Yaobing; Gong, Zhe; Teng, Junfang; Jia, Yanjie (Frontiers in Neurology, 2021)
Background: Many patients with neuromyelitis optica spectrum disorders (NMOSD) experience the adverse consequences of relapse and disability aggravation. Thus, it is necessary to identify sensitive and reliable biomarkers for early prognosis. This study investigated whether serum homocysteine (Hcy) level was associated with the risk of relapse or poor prognosis in first-attack NMOSD patients. Methods: We enrolled 161 first-attack NMOSD patients in this retrospective study. We reviewed their medical records and evaluated their initial Expanded Disability Status Scale (EDSS). Clinical outcomes were measured by the final EDSS and the relapse rate. The association between Hcy levels and EDSS score at last follow-up was analyzed by binary logistic regression. The association between Hcy levels and relapse rate was assessed by Cox regression analysis. Receiver operating characteristic (ROC) curve analysis was used to predict the target value of Hcy reduction. Results: Compared with the high Hcy group, the final EDSS score in the low Hcy group was significantly lower (median: 0.5 vs. 2.5, P < 0.001). The relapse rate differed significantly between these groups (30.6 vs. 50.0%, P = 0.023). Multivariate analysis showed that the initial EDSS score (odds ratio [OR] 3.03, 95% confidence interval [CI] 2.07–4.45, P < 0.001) and serum Hcy level (OR 1.13, 95%CI 1.04–1.22, P = 0.002) were significantly associated with poor prognosis in NMOSD patients. Additionally, multivariate analysis showed that serum Hcy level (hazard ratio 1.06, 95%CI 1.04–1.09, P < 0.001) was an independent predictor of the risk for relapse in NMOSD. The 12-month relapse rate of the high Hcy group was 34.8%, and 50% of high Hcy patients relapsed within 35 months after the first onset. A serum Hcy level exceeding 14.525 μmol/L indicated a high risk of relapse, with a sensitivity of 43.7%, specificity of 90.0%, and area under the ROC curve of 0.674 (95%CI 0.59–0.76, P < 0.001). Conclusion: Serum Hcy level is an independent predictor of relapse and poor prognosis in first-attack NMOSD patients. Early monitoring and reduction of serum Hcy levels may be of great significance in the prevention of disease relapse and severe disability.